2005
DOI: 10.1097/01.mlg.0000181502.07160.86
|View full text |Cite
|
Sign up to set email alerts
|

Confocal microscopy of the Peripheral Gustatory System: Comparison between Healthy Subjects and Patients Suffering from Taste Disorders during Radiochemotherapy

Abstract: In conclusion, in RCT patients with taste disorders, LSM indicates changes of epithelia of fungiform papilla but no changes of the taste bud structure. Damage of the chorda tympani nerve by scattered rays, direct or indirect mucotoxic effects of chemotherapeutic agents, and covering of taste pores by epithelial cells are likely reasons for taste loss during RCT.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
43
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(45 citation statements)
references
References 12 publications
1
43
0
1
Order By: Relevance
“…The results indicated that epithelial changes in the fungiform papilla (but not in the taste bud structure) were predictive of dysgeusia [18].…”
Section: Combined Modality Therapy (Rt +/− Ct)mentioning
confidence: 93%
“…The results indicated that epithelial changes in the fungiform papilla (but not in the taste bud structure) were predictive of dysgeusia [18].…”
Section: Combined Modality Therapy (Rt +/− Ct)mentioning
confidence: 93%
“…The shelf life is much longer than that of liquid solutions. Although this test has already resulted in a series of publications [14,22,34,36,39] and was proven reliable concerning the investigation of tongue side differences [21,29] and gustatory testing before and after an intervention [30,37], the initially proposed test procedure had some shortcomings. First, the paper by Mueller et al [36] was based on solely 69 observations.…”
Section: Introductionmentioning
confidence: 98%
“…If FPs are biopsied, it becomes impossible to observe the same FP. In this context, confocal laser microscopy has made it possible to observe the human taste buds noninvasively and in vivo (7,8). Furthermore, a marked advantage of confocal laser microscopy is that the same FP can be observed repeatedly.…”
mentioning
confidence: 98%
“…In another study, no taste pore was detectable in patients with taste disorders during radiochemotherapy. In deeper sections, however, taste buds were present (8). Thus, the taste pore and taste bud structures could be visualized in vivo by confocal laser scanning microscopy.…”
mentioning
confidence: 98%